Fescue Hay Cost-Return Budget in Central and Eastern Kansas - Ibendahl, Gregg; Shoup, Douglas; O'Brien, Daniel M.; Duncan, Stewart R. (My University, 2015)
This publication provides estimated cost and returns for forward farm planning for fescue hay in central and eastern Kansas.
MF2146_2015_04
Keywords: MF2146; Crops; Economics; MF